(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The heritability of rheumatoid arthritis (RA) is approximately 40% to 65% for seropositive RA and 20% for seronegative RA. The risk of developing RA has been associated with human leukocyte antigen HLA-DRB1 alleles: HLA-DRB1*04, HLA-DRB1*01, and HLA-DRB1*010 in deferent ethnocentrism. These HLA-DRB1 alleles contain a stretch of conserved five amino acid sequence, the shared epitope (SE), in the third hypervariable region of their DRB1 chain, which has been associated with the risk of developing Aim of the study: to study the possible association of HLA-DRB1 gene polymorphism of Arabic ethnocentrism PA patients in Babylon Province, Iraq. Patients and methods: The present case control study was conducted on sixty one patients (18 males and 43 females) of Arabic ethnocentrism RA patients admitted to Rheumatoid Unit in Merjan Teaching Medical City, Babylon Province, Iraq, as well as 127 apparently healthy control subjects (41 males, 86 females) as control group. Results: The risk of HLAD-RB1*01 allele was assessed through calculation of odds ratio (OR) which was estimated to be 1.95 (95 % confidence interval of 1.03 to 3.70). The risk of HLAD-RB1*04 allele was assessed through calculation of odds ratio (OR) which was estimated to be 4.46 (95 % confidence interval of 2.32 to 8.55). The risk of HLAD-RB1*010 allele was assessed through calculation of odds ratio (OR) which was estimated to be 3.12 (95 % confidence interval of 1.39 -7.00). Conclusion: The current study documented that RA is significantly associated with the locus HLA-DRB1* and allelic groups HLA-DRB1*01, HLA-DRB1*04 and HLA-DRB1*010 in Iraqi patients with RA